Atributos de espécies arbóreas e a facilitação da regeneração natural em plantio heterogêneo de mata ciliar - De Melo, Antonio Carlos Galvão; Daronco, Camila [UNESP]; Ré, Danilo Scorzoni [UNESP]; Durigan, Giselda (My University, 2015)
Ecological interactions among species, both positive and negative, have a strong influence on the structure of plant communities and their comprehension can contribute to the improvement of techniques for ecological restoration. Facilitation of natural regeneration by trees planted in riparian forest restoration in the Cerrado region was the subject of this study. We sampled 91 trees ten years old, belonging to six species representing different functional groups by seed dispersal syndrome, deciduousness, and Nitrogen-fixing ability. Gaps created by failures in the initial planting were sampled as controls. Density and richness of regenerating plants were use as response variables. The species, their functional attributes, tree size and the environment under the canopy (grass biomass, light flux and soil moisture) were used as explanatory variables. Density and richness of woody plants under the different species varied greatly among species. Variation was partially explained by deciduousness, but mostly by canopy size and shape, which modify the availability of light to plants in the understory. Restoration of riparian forests in the cerrado region by planting trees should prioritize species with the following attributes: large canopy, fast growing, and a certain level of deciduousness. Such species can trigger natural regeneration processes under their canopies and therefore should accelerate restoration.
Tree species attributes and facilitation of natural regeneration in heterogeneous planting of riparian vegetation
Keywords: Ecological filters; Plant-plant interactions; Restoration ecology; Riparian forests; Sssembly rules